Creating the Adiwiyata School with Waste and Environmental Management at SDN Nglumber II Kepohbaru, Bojonegoro - Aldira Mara Ditta Caesar Purwanto; Rohmatul Faizah (Nusantara Science and Technology Proceedings, 2022)
The Adiwiyata program is a place for schools to learn and raise awareness for educators, education staff, students, and the community around schools to protect the environment and encourage sustainable development. So that it can create a school that is environmentally friendly and cultured. The Adiwiyata program itself has been implemented by the Ministry of Environment and continues by the Ministry of Environment and Forestry which aims to create schools that care and are environmentally cultured through activities of coaching, assessing, and awarding Adiwiyata to schools. The guidelines for implementing the Adiwiyata program are regulated in the Minister of Environment Regulation Number 5 of 2013. In line with the Adiwiyata program, SDN Nglumber II, located in Kepohbaru District, Bojonegoro Regency, has the goal of becoming an Adiwiyata School. Although schools have great potential, to achieve this, many things need to be prepared. This service aims to provide socialization and assistance to increase environmental knowledge to school residents, especially students before Adiwiyata activities will resume. It is intended that the Adiwiyata activities will be successful and sustainable so that the objectives of the Adiwiyata program can be achieved. The process of a series of ABDIMAS activities starts from the preparation stage, namely situation analysis, then continues with Forum Group Discussion (FGD) in small groups after which counseling is carried out. With the implementation of this service activity, teacher knowledge about the school environment to support the implementation of the Adiwiyata program increases. The knowledge and skills that have been possessed are expected to be transmitted and become an example for elementary schools around the City of Bojonegoro for the realization of Adiwiyata schools.